How adverse childhood experiences impact the professional quality of life of residential care workers: resilience as a mediator for burnout, secondary traumatic stress, and compassion satisfaction - Milne, Lise; Ratushniak, Adrienne; Nguyen, Hannah (Frontiers in Child and Adolescent Psychiatry, 2024)
Introduction The well-being of trauma-affected children and youth in residential care settings is contingent upon the well-being of the workers who care for them, who are increasingly expected to provide care in a trauma-informed manner. The well-being of residential care workers (RCWs) may be impacted by their own histories of adversity, their capacity individually and collectively to navigate to resources that sustain their well-being (resilience), and current perceptions of their professional quality of life. Objective This study aimed to fill a research gap by canvassing the perspectives of RCWs to determine what and how they need to be supported in their work. We sought to better understand what personal (adverse childhood experiences, resilience) and professional (compassion satisfaction, burnout, secondary traumatic stress) experiences and capacities they bring into their work that might impact the quality of care they provide to children and youth. Method A sample of 226 residential care workers from four residential care organizations across three Canadian provinces completed a self-report questionnaire to provide a portrait of their history of adverse childhood experiences as measured by the ACE questionnaire, which included two additional questions reflecting the more nuanced and expanded understanding of potential adversity in childhood in the Canadian context; their resilience, as measured by the Adult Resilience Measure; and compassion satisfaction, burnout, and secondary traumatic stress, as measured by the Professional Quality of Life Measure. Mediation was conducted to examine whether and how resilience mediated the relationship between ACEs and professional quality of life indicators. Results (1) RCWs reported experiencing ACEs at rates much higher than general population and norm samples, especially regarding the experience of 4–5+ ACEs, known to be a threshold for increased severity in negative outcomes; (2) RCWs experienced levels of resilience and indicators of professional quality of life similar to those in other human services professions serving trauma-impacted individuals; and (3) RCW resilience significantly mediated the relationship between ACEs and compassion satisfaction, burnout, and secondary traumatic stress, and had a significant total effect for the relationship between ACEs and secondary traumatic stress. These results suggest the importance of enhancing RCW resilience in multiple ways, mainly in their professional contexts. Recommendations for resilience enhancement and suggestions for future research are provided.